Pengaruh Infrastruktur Sosial dan Ekonomi terhadap Pertumbuhan Ekonomi Indonesia Tahun 2015 - 2019 - Kristian Brilyawan; Purbayu Budi Santosa (Universitas Diponegoro, 2021)
Infrastructure development in Indonesia has been going on for a long time and at a fairly large cost. The contribution of infrastructure development is quite significant in increasing economic growth, but there are still problems faced by our country. This study aims to determine the influence and contribution of economic and social infrastructure to economic growth in Indonesia, which is represented by Gross Regional Domestic Product per capita. Panel data regression analysis is used to see the magnitude of the influence of infrastructure on economic growth in Indonesia. The infrastructure studied includes: length of roads, distributed electricity, clean water that is distributed, health described by Life Expectancy (AHH), and education described by the Average Length of School (RLS). The analysis was carried out using panel data with a random effect model in 34 provinces in Indonesia and over a period of 5 years (2015-2019). The results obtained are that roads and education have a significant effect on economic growth. Electricity, clean water, and health do not have a significant effect.economic infrastructure, social infrastructure, economic growth